The welcoming experience of the arrival space in museums - Guo, Sifan (2022)
Since the world first public museum opened in the late seventeenth century in Oxford, many efforts have been made on welcoming visitors. Nowadays, the museum should not only focus on the increasing number of visitors, but also should consider how to provide a more comfortable and popular visiting experience to various people from every angle, such as the people with different cultures, religions, ethnicities and educational backgrounds, and attracts more repeat visitors. Therefore, the arrival space is particularly important as the first stop for people to understand the museum.